2022
DOI: 10.1126/scitranslmed.abo3357
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive, sustained-release relaxin-2 microparticles reverse arthrofibrosis

Abstract: Substantial advances in biotherapeutics are distinctly lacking for musculoskeletal diseases. Musculoskeletal diseases are biomechanically complex and localized, highlighting the need for novel therapies capable of addressing these issues. All frontline treatment options for arthrofibrosis, a debilitating musculoskeletal disease, fail to treat the disease etiology—the accumulation of fibrotic tissue within the joint space. For millions of patients each year, the lack of modern and effective treatment options ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…To improve the metabolic efficiency of the RLX-2, follow-up studies found that RLX-loaded Poly lactide coglycolide (PLGA) microparticles (MPs) could effectively exert the anti-fibrotic effect of RLX and significantly increased the duration of RLX activity. The study by Kirsch et al (2022) showed that RXFP1 was also expressed in periarticular tissue of the shoulder joint of FS patients. These results suggested RLX might represented a novel therapeutic target for the treatment of frozen shoulder.…”
Section: Regulation and Mechanism Of Rlx In Fibrotic Ligament Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…To improve the metabolic efficiency of the RLX-2, follow-up studies found that RLX-loaded Poly lactide coglycolide (PLGA) microparticles (MPs) could effectively exert the anti-fibrotic effect of RLX and significantly increased the duration of RLX activity. The study by Kirsch et al (2022) showed that RXFP1 was also expressed in periarticular tissue of the shoulder joint of FS patients. These results suggested RLX might represented a novel therapeutic target for the treatment of frozen shoulder.…”
Section: Regulation and Mechanism Of Rlx In Fibrotic Ligament Diseasesmentioning
confidence: 99%
“…Fibrosis was a chronic disease requiring long-term use of RLX ( Samuel et al, 2005 ; Blessing et al, 2019 ). However, the half-life of RLX is only 1.6 h, which limits its clinical application ( Kirsch et al, 2022 ). Therefore, RLX must be administered non-intravenously, usually requiring several times a day.…”
Section: Challenges Of Rlx In Fibrotic Ligament Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…It also plays a role in vascular dilation and the maintenance of sperm motility. These effects occur through the activation of relaxin-mediated signaling pathways, including the pERK-nNOS-NO-cGMP, PI3K-AKT-eNOS, cyclic adenosine monophosphate (cAMP)-protein kinase A, nuclear factor kappa B (NF-κB), peroxisome proliferator-activated receptor gamma, and vascular endothelial growth factor (VEGF) signaling pathways, as well as the inhibition of the tumor growth factor (TGF)-β1/pSmad pathway [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. RLN3 is a neuropeptide primarily synthesized in the brain and maps to chromosome 19p13.3 [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%